RelayVio: mobile application for documenting domestic violence - Noris Mohd Norowi,; Siti Norhanida Hairudin,; Lili Nurliyana Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2021)
RelayVio is designed and developed as android based mobile applications for all users, particularly users of domestic violence victims and their families in Malaysia. The main function of this app is to encourage domestic violence victims to document evidence of violence by way of writing notes, capturing images and recording dates and times of the occurrence. The app also allows victims to sending messages to a domestic violence hotline (Talian Nur), or can directly connect to 999 in the event of an emergency. The app also aims to educate the general public on the signs, dangers and help they can get relating to domestic violence abuse, through the use of animation (3D stop motion). getting information about the act of domestic violence. The method used in the development of mobile applications is ADDIE, which consists of analysis, design, system development, implementation and evaluation. An interview with a sociologist was conducted as an expert review, as well as a usability study of the app. Results show that the majority of the participants agreed that RelayVio app will be able to facilitate victims of domestic violence to gather information and keep documentation of the abuse as a form of evidence against their abusers.